Methods of mathematical induction - Sominskii, I.S.; MOSS Halina (New York Blaisdell publishing Company, 1961)
Induction in Geometry discusses the application of the method of mathematical induction to the solution of geometric problems, some of which are quite intricate. The book contains 37 examples with detailed solutions and 40 for which only brief hints are provided. Most of the material requires only a background in high school algebra and plane geometry; chapter six assumes some knowledge of solid geometry, and the text occasionally employs formulas from trigonometry.
Keywords: Mathematics; Problems and Exercises; Geometry